2021
DOI: 10.1021/acs.inorgchem.1c00444
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Ligand Cobalt(III) Complexes of a Naturally Occurring Coumarin and Phenanthroline Bases as Mitochondria-Targeted Dual-Purpose Photochemotherapeutics

Abstract: The bioessential nature of cobalt and the rich photochemistry of its coordination complexes can be exploited to develop potential next-generation photochemotherapeutics. A series of six novel mixed-ligand cobalt­(III) complexes of the formulation [Co­(B)2(L)]­ClO4 (1–6), where B is an N,N-donor phenanthroline base, namely, 1,10-phenanthroline (phen in 1 and 4), dipyrido­[3,2-d:2′,3′-f]­quinoxaline (dpq in 2 and 5), and dipyrido­[3,2-a:2′,3′-c]­phenazine (dppz in 3 and 6), and L is an O,O-donor dianionic ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…The complexes showed remarkable light-induced toxicity with negligible dark toxicity. [92] Vanadium complexes also produced hydroxyl radical upon irradiation as shown by Chakravarty and his group by synthesizing four oxovanadium (IV) complexes with curcuminoids (55-58). The Cytotoxicity was assessed in HeLa, HepG2 and 3T3 cells in the dark as well as in visible light.…”
Section: Lmct Transition and Hydroxyl Radical Generationmentioning
confidence: 96%
“…The complexes showed remarkable light-induced toxicity with negligible dark toxicity. [92] Vanadium complexes also produced hydroxyl radical upon irradiation as shown by Chakravarty and his group by synthesizing four oxovanadium (IV) complexes with curcuminoids (55-58). The Cytotoxicity was assessed in HeLa, HepG2 and 3T3 cells in the dark as well as in visible light.…”
Section: Lmct Transition and Hydroxyl Radical Generationmentioning
confidence: 96%
“…Worth noting are cobalt (III) complexes [Co(B) 2 (L)]ClO 4 9-11 ( Table 1 ) prepared by Sakar and co-workers in a two-step procedure, starting from N , N -donor bases: 1,10-phenanthroline ( phen ), dipyrido [3,2-days:2′,3′- f ]quinoxaline ( dpq ) or dipyrido [3,2- a :2′,3′- c ]phenazine base ( dppz ) and naturally occurring esculetin (6,7-dihydroxycoumarin) as dianionic O , O -donor, as well as cobalt (II) chloride and sodium perchlorate in the presence of triethylamine ( Sarkar et al, 2021 ). These new complexes, due to their high visible light-triggered cytotoxicity against cervical cancer cell line (HeLa) and human breast cancer cell line (MCF-7), represent an interesting example of potent next-generation photochemotherapeutics.…”
Section: Anticancer Complexesmentioning
confidence: 99%
“…It has been established that the metal complexation of curcumin increases its stability and bioavailability. Moreover, curcumin is reported as a good photosensitizer due to its efficient singlet oxygen generation ability under visible light . Therefore, in recent years, several curcumin-based metal complexes have been reported for PDT. , Several curcumin complexes of V­(IV), Fe­(III), Co­(II), Co­(III), Pt­(II), Ru­(II), Ir­(III), Os­(II), Rh­(III), etc. are explored as photosensitizers for PDT application, but the example of Zn­(II)-curcumin complexes in PDT is very rare. , To the best of our knowledge, Chakraborty et al reported the only Zn­(II)-curcumin complex with BODIPY as a pendant for PDT activity .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, several curcumin-based metal complexes have been reported for PDT. , Several curcumin complexes of V­(IV), Fe­(III), Co­(II), Co­(III), Pt­(II), Ru­(II), Ir­(III), Os­(II), Rh­(III), etc. are explored as photosensitizers for PDT application, but the example of Zn­(II)-curcumin complexes in PDT is very rare. , To the best of our knowledge, Chakraborty et al reported the only Zn­(II)-curcumin complex with BODIPY as a pendant for PDT activity . Thus, although curcumin-based Zn­(II) complexes have been well-explored as cancer chemotherapeutics, their use as photosensitizers for PDT has not been well-explored.…”
Section: Introductionmentioning
confidence: 99%